Performance Analysis of Uplink NOMA based Full-Duplex UAV for Indoor Disaster Environment - Kang, Junghwa; Kashihara, Hisato; Sumantyo, Josaphat Tetuko Sri; Kim, Jae Hyun (International Conference on ICT Convergence, 2021)
Unmanned aerial vehicle (UAV) can be used to serve as aerial wireless base stations when the cellular network collapses. Most of the studies on UAV-served communication assumed that the users are located at outdoor and their position are coordinated as two-dimensional. However, most user traffic occurs indoors and a communication error is caused by a low throughput may cause casualties in indoor emergency. Recent studies that handle indoor disaster situation, only considered the UAV coverage. Therefore, practical research is needed for user's safety. In this paper, we propose uplink non-orthogonal multiple access for based full-duplex UAV increasing throughput in indoor disaster situation. We consider and modify indoor-to-outdoor path loss model for indoor users served by outdoor UAV, and the altitude of UAV ensuring signal to interference plus noise ratio. Simulation results show that the proposed model improves the performance of throughput than conventional scheme.
Keywords: Cellular network; Disaster situations; Full-duplex; Multiple access; Non-orthogonal; Non-orthogonal multiple access; Outdoor-to-indoor; Path loss models; Performances analysis; Wireless base stations; full-duplex; non-orthogonal multiple access; outdoor-to-indoor; path loss model; Unmanned aerial vehicles